SOSIALISASI LEMBAGA PENJAMIN SIMPANAN (LPS) DALAM RANGKA MENINGKATKAN MINAT MENABUNG MASYARAKAT - Usnatun Khasanah (2021)
The existence of banking activities at this time is very important. All aspects of life that occur at this time must have something to do with these activities. Public trust in banks to carry out their functions is increasing and growing. In accordance with law number 24 of 2004, the Deposit Insurance Corporation was established or generally called LPS, the institution is independent, in collaboration with the Financial Services Authority. Due to the monetary crisis that hit Indonesia in 1998, the public, especially customers in banking, decreased their level of trust in banking. With the existence of LPS whyhich has been operating since September 22, 2005 until now, it guarantees every customer 2,000,000,000 (two billion rupiah). The role of the Deposit Insurance Corporation is to socialize banking to the public regarding the guarantees, interest rates, and security offered. Banks guaranteed by the Deposit Insurance Corporation usually provide education on the existence of a guarantor. Conducting a review to fulfill the Final Assignment of the Deposit Insurance Corporation to obtain sources of information through interviews with resource persons through questions posed by the author. Keywords: Socialization, Deposit Insurance Corporation, Saving Interest.